Find the second-order partial derivatives

Showing results 1 through 10 of 184,343.
  1. find the second-order partial derivatives of f(x,y)=x^3 + x^2y^2 + y^3 + x+yand show that the mixed partial derivatives fxy and
    1. answers icon 0 answers
    2. maggie asked by maggie
    3. views icon 597 views
  2. Find the second-order partial derivatives of the function.f(x,y) = x^5 + x^2y + x + 5 a. fxx = ? b. fyy = ? c. fxy = ? d. fyx =
    1. answers icon 1 answer
    2. Mia asked by Mia
    3. views icon 500 views
  3. Find the first order partial derivatives. z=ln(xy-sqrt(x^2-y^2)
    1. answers icon 1 answer
    2. jay asked by jay
    3. views icon 1,313 views
  4. Find all the first and second order partial derivatives of the function f(x,y) = 2x^3+ 3x^2 y^2 + 3x + 2/y + 4
    1. answers icon 1 answer
    2. Anonymous asked by Anonymous
    3. views icon 2,783 views
  5. Find the second-order partial derivatives of the function.f(x,y) = x^5 + x^2y^2 + y^4 + x + y a. fxx = ? b. fyy = ? c. fxy = ?
    1. answers icon 1 answer
    2. Mia asked by Mia
    3. views icon 486 views
  6. Consider the partial derivativesfx(x,y)=4x3y7−20x3y, fy(x,y)=7x4y6−5x4. Is there a function f which has these partial
    1. answers icon 1 answer
    2. val asked by val
    3. views icon 123 views
  7. What are the critical points for g(x,y)=x^3+y^3+(9/(xy)) and are they maximums or minimums? I understand I find the partial
    1. answers icon 1 answer
    2. anonymous asked by anonymous
    3. views icon 257 views
  8. a)find the first partial derivatives of f(x y)= x √1+y^2b)find the first partial derivatives of f(x,y)= e^x ln y at the point
    1. answers icon 2 answers
    2. maria asked by maria
    3. views icon 628 views
  9. Find out the partial derivative w.r.t 'x' and 'y' off (x,y) = log(y) x Now, log(y) x = ln x / ln y Partial Diff w.r.t 'x' = 1/ x
    1. answers icon 1 answer
    2. Akki asked by Akki
    3. views icon 1,650 views
  10. Calculate all four second-order partial derivatives of f(x,y)=sin(5x/y). fxx(x,y)= fxy(x,y)= fyx(x,y)= fyy(x,y)=
    1. answers icon 1 answer
    2. val asked by val
    3. views icon 90 views